Do Financial Idiosyncratic Deals Make Good Organizational Citizens? A Moderated Model of Perceived Organizational Justice - Kimwolo , A. (African Journal of Education,Science and Technology (AJEST), 2019)
This paper aims to determine the effect of financial idiosyncratic deals on organizational citizenship behaviour (OCB) among tied life insurance agents in Kenya. It aims to address the gap in literature on i-deals OCB through the intermediate mechanism of perceived organizational justice. The objectives of the study were to find out the effect of financial i-deals on OCB and to analyze the moderating effect of perceived organizational justice on the relationship between i-deals and OCB among tied life insurance agents. Standard multiple regression analysis was used to test the hypotheses from data collected from a study from 498 employees and 48 managers of tied life insurance agents in Kenya. The study findings showed a positive interaction between financial i-deals and perceived organizational justice. Hence there was a moderating effected of Perceived Organizational Justice (POJ) on OCB. The cross-sectional collection of data weakens the author’s claim of causality between the variables in focus. The study used both stratified and simple random sampling strategies. The main finding from the study was that POJ moderates the relationship between i-deals and OCB. The study extends literature on the moderating effect of POJ on the relationship between financial i-deals and OCB. It concludes that POJ moderates the relationship between financial i-deals and OCB. It recommends that organizations, particularly tied life insurance firms should grant their employees financial i-deals fairly in order for co-workers to reciprocate OCB. Financial i-deals granted fairly to all co-workers enhance reciprocation of OCB in the work place hence create beneficial social exchange relationships at work place. This is the first study to investigate a moderating effect on the relationship between financial idiosyncratic deals and OCB.